A cost analysis of COVID-19 vaccination: a comparison between mRNA-based and inactivated virus vaccines - Samsudin, Khalsom; Mahmud, Aidalina; Ahmad, Norliza (Universiti Putra Malaysia Press, 2024)
Introduction: COVID-19 vaccination is considered a primary preventive measure to combat the COVID-19 pandemic. Several types of COVID-19 vaccines were developed, among them the mRNA-based vaccine and the inactivated virus vaccine. Different COVID-19 vaccines have different purchase price and require different logistics system, which translate into different estimated vaccination costs. Therefore, this study aims to estimate the cost of COVID-19 vaccination using the mRNA-based vaccine compared to the inactivated virus vaccine to assist future decision-making related to COVID-19 vaccination. Methods: Direct costs for per-dose vaccination for both vaccines were estimated from the health provider’s perspective using the microcosting approach. Vaccination pathways were constructed for both the mRNA-based and the inactivated virus vaccine based on activities involving the acquisition, transportation, storage, and vaccine injection processes. Cost value was obtained from purchase documents, asset records, and market surveys. Results: The estimated costs for COVID-19 vaccination were RM 69.71 per dose for the mRNA-based vaccine and RM 91.68 per dose for the inactivated virus vaccine. The difference in estimated vaccination costs was mainly driven by the difference in the vaccine purchase costs which was higher for the inactivated virus vaccine. Conclusion: COVID-19 vaccination using the mRNA-based vaccine incur was estimated to incur lower total costs to the health provider compared to the inactivated virus vaccine during the pandemic.